2020
DOI: 10.3390/ijms21093232
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of lncRNA XLOC-2222497, AKR1C1, and Progesterone in Porcine Endometrium and Pregnancy

Abstract: The endometrium is an important tissue for pregnancy and plays an important role in reproduction. In this study, high-throughput transcriptome sequencing was performed in endometrium samples of Meishan and Yorkshire pigs on days 18 and 32 of pregnancy. Aldo-keto reductase family 1 member C1 (AKR1C1) was found to be a differentially expressed gene, and was identified by quantitative real-time PCR (qRT-PCR) and Western blot. Immunohistochemistry results revealed the cellular localization of the AKR1C1 protein in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 85 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…All pigs were raised under the same conditions, with a standardized feeding regimen and free access to water. On days 18 and 32, two Yorkshire sows and two Meishan sows were slaughtered at each time-point, and the endometria were taken [ 23 ]. In our research, all animal experiments were conducted according to the Care and Use of Laboratory Animals Guidelines in China.…”
Section: Methodsmentioning
confidence: 99%
“…All pigs were raised under the same conditions, with a standardized feeding regimen and free access to water. On days 18 and 32, two Yorkshire sows and two Meishan sows were slaughtered at each time-point, and the endometria were taken [ 23 ]. In our research, all animal experiments were conducted according to the Care and Use of Laboratory Animals Guidelines in China.…”
Section: Methodsmentioning
confidence: 99%
“…Yang et al (2020) analyzed lncRNA and mRNA in male sheep pituitary and found that 5 candidate lncRNAs and their targeted genes enriched in growth and reproduction related pathways [16]. Su et al (2020) screened differential lncRNA through high-throughput sequencing, concluded that XLOC-2222497 and its target AKR1C1 could interact with progesterone in porcine endometrium for controlling pregnancy maintenance [17]. These studies indicated the presence and role of lncRNA in reproductive tissues.…”
Section: Introductionmentioning
confidence: 97%
“…Tens of thousands of lncRNAs have now been identified in humans, zebrafish, and mice (Zhao et al, 2016;Hu et al, 2018). LncRNAs can mediate the regulation of target genes by interacting with RNA, DNA, or proteins and are known to play a role in reproduction (Su et al, 2020), embryonic development (Kuang et al, 2020), sex differentiation (Cai et al, 2019), immunity (Liu et al, 2020), and metabolism (Li et al, 2020) at the transcriptional, posttranscriptional, and epigenetic levels. Other studies, involving fish, have shown that lncRNAs also play an important role in the network regulation of gene expression to cope with stress (Dettleff et al, 2020).…”
Section: Introductionmentioning
confidence: 99%